On the robustness of fixed effects and reated estimators in correlated random coefficient panel data models - Jeffrey M. Wooldridge (Centre for Microdata Methods and Practice (cemmap), 2003)
I show that a class of fixed effects estimators is reasonably robust for estimating the population-averaged slope coefficients in panel data models with individual-specific slopes, where the slopes are allowed to be correlated with the covariates. In addition to including the usual fixed effects estimator, the results apply to estimators that eliminate individual-specific trends. Further, asymptotic variance matrices are straightforward to estimate. I apply the results, and propose alternative estimators, to estimation of average treatment in a general class of unobserved effects models.
Keywords: 330; Average Treatment Effect; Fixed Effects; Random Coefficient; Schätztheorie; Zufallsvariable